A multicenter survey on post‐transplant lymphoproliferative disorders in pediatric heart transplant recipients: A case for development of consensus guidelines for screening, surveillance, and treatment?. (16th May 2020) - Weisert, Molly; Harake, Danielle; Hede, Sannya; Russell, Matthew; Alejos, Juan; Menteer, JonDavid
Abstract: Post‐transplant lymphoproliferative disorders (PTLD) are the main malignancy seen after pediatric heart transplant and are a significant cause of morbidity and mortality. Prior to the development of detailed guidelines, we sought to identify trends in screening, diagnosis, and treatment of pediatric PTLD. All Pediatric Heart Transplant Society (PHTS) institutions were surveyed. No identifiable patient information was shared. From 56 PHTS centers, 22 responses were received (39.3%). 100% agree PTLD cannot be diagnosed solely based on elevated Epstein‐Barr virus (EBV) load. All respondents routinely screen for EBV by blood PCR, but frequency of screening varies. There was intermediate consensus regarding the use of computed tomography (CT) and/or positron emission tomography (PET) in surveillance management for PTLD. Most centers require a diagnostic biopsy before initiating new treatment for PTLD (14 of 18, 77.8%), but many reduce immune suppression based on elevated EBV without pathologic PTLD (16 of 22, 72.7%). Beyond immune modulation, rituximab is most commonly used (9 of 13, 69.2%). Consultation with oncology is common (17 of 17, 100%), but timing varies widely. Our survey highlights significant elements of agreement and significant practice variation among PHTS institutions regarding pediatric PTLD. Reduction of immune suppression prior to pathologic diagnosis of PTLD is a common management strategy. When this fails, rituximab is used, but is most often reserved until after confirmation of the diagnosis. Oncology subspecialists are commonly involved in these cases. Our findings highlight the need to develop improved guidelines for evaluation and treatment of pediatric PTLD.